Handling of incongruences in music notation during singing or playing. (February 2021) - Chitalkina, Natalia; Puurtinen, Marjaana; Gruber, Hans; Bednarik, Roman
During music reading, performers create expectations of the upcoming music. When these expectations are violated due to changes in the notation, performers have to adjust their reading and adapt their motor responses to match this new information. In this study, we examine how selected background, outcome, and process measures reflect the successful handling of incongruences during music reading. Twenty-four performers were tasked with singing or playing versions of "Mary had a little lamb" in two different tonalities. Some versions contained a surprising element: a bar shifted down a tone. Selected outcome and process measures, such as performance accuracy and eye-movements during music reading (eye-time span, duration of first-pass fixations and pupil dilation), were analyzed. In sum, incongruence in music notation not only increased the number of performance mistakes, but incongruent melodies also led to micro-level changes in the reading processes. We propose that understanding the cognitive strategies for successful music reading requires going beyond the more traditional outcome measures and focus on the detailed analyses of the reading process itself.